Some properties of maximal open sets - Fumie Nakaoka; Nobuyuki Oda (International Journal of Mathematics and Mathematical Sciences)
Some fundamental properties of maximal open sets are obtained, such as decomposition theorem for a maximal open set. Basic properties of intersections of maximal open sets are established, such as the law of radical closure.